The Impact of Drying and Salting on the Fish Resilience and Quality - Rani, Rani; Sholihah, Nurhidayati; Mutmainah, Fadzilatul; Sopiah, Sopiah; Rahmi, Rahmi; Aisyah, Nur; Marta, Eni (International Journal of Natural Science and Engineering, 2022)
Drying fish is one way of preserving fish by reducing the water content of fish so that the activity of microorganisms can be reduced. Preservation by drying is intended to extend the shelf life of fish. Many fish species have used the drying method for a long time. This study aimed to analyze the effect of drying on salted and unsalted fish to test the resistance and quality of fish. Making salted fish is the simplest preservation with low cost. The characteristics of fish that have a neutral pH, soft texture, and high nutritional content make fish a good medium for bacterial growth. Most Indonesian people manage fish to overcome the damage, including those processed into salted fish. Salted fish is one form of traditional fish processed products with drying and salting technology. Based on the study's results, it was concluded that salted fish that was dried for more than 12 hours of heating in the sun produced products that were acceptable to consumers, while drying under 8 hours produced products that consumers did not accept. There is a need for further testing on the shelf life and the need for the use of hygienic packaging. Based on the analysis, the concentration of salt and time of salting did not significantly affect the texture and aroma.